PERAN NILAI-NILAI ETIKA DALAM MENINGKATKAN REPUTASI PERUSAHAAN - Aprinawati; Simbolon, Laksmi Yanti Br; Sianipar, Christina Br (Puteri Hijau : Jurnal Pendidikan Sejarah, 2025)
This study discusses the role of ethical values ​​in improving corporate reputation. Business ethics that are applied consistently and transparently serve as the main foundation in building trust and loyalty of customers, business partners, and other stakeholders. Through the application of ethical principles such as integrity, honesty, social responsibility, and compliance with norms, companies can create a positive image that supports business sustainability and competitiveness in the market. This study uses a literature study approach with qualitative analysis of literature related to business ethics and corporate reputation. The results of the study show that business ethics not only have an impact on corporate image, but also strengthen long-term relationships with customers and increase the overall value of the company. Therefore, investing in ethical values ​​is an important strategy to maintain and improve corporate reputation in an increasingly complex and digital business era.